KEBIJAKAN KEHUTANAN DAN AKIBATNYA BAGI MASYARAKAT LOKAL - Siburian, Robert (Jurnal Masyarakat dan Budaya, 2004)
This article seeks to explain the relations between the Forest Policy and people who live in forest area. Despite the fact that Indonesia has a vast forest area with an abundance of economic resources that has been exploited, the fate of people who make their living from it is almost forgotten. Most of forest policies have been made and implemented to the disadvantages of the people who live in the area.